Factors influencing utilization of different types of sulphonylureas amongst type 2 diabetes patients - Huri, H.Z.; Wei, A.T.L.; Pendek, R.; Sulaiman, C.Z.; Widodo, R.T. (Colegio Farmaceuticos Provincia De Buenos Aires, 2010)
Sulphonylureas (SUs) are commonly prescribed in Malaysia and also worldwide. However, very limited information is available on their pattern of use and appropriateness of its utilization. Age, concurrent use of drugs such as beta blocker, salicylate and frusemide and also renal impairment were found to have influence on the selection of different types of SUs.